2004
DOI: 10.1029/2004gl020991
|View full text |Cite
|
Sign up to set email alerts
|

The Eddy Experiment: GNSS‐R speculometry for directional sea‐roughness retrieval from low altitude aircraft

Abstract: We report on the retrieval of directional sea surface roughness, in terms of its full directional mean square slope (including direction and isotropy), from Global Navigation Satellite System Reflections (GNSS-R) Delay-Doppler-Map (DDM) data collected during an experimental flight at 1 km altitude. This study emphasizes the utilization of the entire DDM to more precisely infer ocean roughness directional parameters. In particular, we argue that the DDM exhibits the impact of both roughness and scatterer veloci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…[30] In this paper we have highlighted an inexpensive, passive, dry operational sensor concept for use on coastal platforms and aircraft (for airborne applications focusing on sea state, see, e.g., Zavorotny and Voronovich [2000] as well as Germain et al [2003]). Oceanpal is to provide precise sea level information and sea state, and we believe it will occupy an important niche in operational oceanography and marine operations.…”
Section: Discussionmentioning
confidence: 99%
“…[30] In this paper we have highlighted an inexpensive, passive, dry operational sensor concept for use on coastal platforms and aircraft (for airborne applications focusing on sea state, see, e.g., Zavorotny and Voronovich [2000] as well as Germain et al [2003]). Oceanpal is to provide precise sea level information and sea state, and we believe it will occupy an important niche in operational oceanography and marine operations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, potential applications of GPS reflected signals from the sea surface could compensate these defects of conventional radar techniques. Recently, a number of ocean remote sensing applications have been implemented using GPS signals reflected from the ocean surface (Martin-Neira et al 2001;Rius et al 2002;Germain et al 2004;Komjathy et al 2004;Thompson et al 2005;Gleason et al 2005). For example, Martin-Neira et al (2001) showed the height of sea surface Furthermore, GPS in a bistatic radar configuration can receive the power from a reflected signal for a variety of delays and Doppler values in a glistening zone surrounding a nominal specular reflection point (Garrison et al 1998).…”
Section: Gnss Ocean Remote Sensingmentioning
confidence: 99%
“…It is well known, however, that winddriven waves on the ocean surface have an anisotropic distribution, with the principal axis aligned with the wind direction [8]. For this reason, there are expected to be errors in retrievals assuming an isotropic distribution.…”
Section: Problem Descriptionmentioning
confidence: 99%